Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Keputusan Pendanaan, dan Kebijakan Dividen terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Sulistyani, Maharani Tri, Drs. Eko Sugiyanto, M.Si (2017)
The aim of this research was to analyzed the effect of managerial ownership, institutional ownership, financing decisions, and dividend policy on the firm value. Population of this research was all of manufacturing firms listed on the Indonesia Stock Exchange the period 2012-2015. The sampling method used in this research was purposive sampling with the total sample as much as 45 companies. Data analysis used by multiple regression analysis. Meanwhile the regression model has been examined by a classical assumption of regression analysis. The result show that financing decisions affect the firm value while managerial ownership, institutional ownership, and dividend policy not affect the firm value.